Microfluidic nozzle device for ultrafine fiber solution blow spinning with precise diameter control. Issue 15 (27th June 2018) - Hofmann, Eddie; Krüger, Kilian; Haynl, Christian; Scheibel, Thomas; Trebbin, Martin; Förster, Stephan
Abstract : We present a microfluidic nozzle device for the controlled continuous solution blow spinning of ultrafine fibers. Abstract : We present a microfluidic nozzle device for the controlled continuous solution blow spinning of ultrafine fibers. The device is fabricated by soft lithography techniques and is based on the principle of a gas dynamic virtual nozzle for precise three-dimensional gas focusing of the spinning solution. Uniform fibers with virtually endless length can be produced in a continuous process while having accurate control over the fiber diameter. The nozzle device is used to produce ultrafine fibers of perfluorinated copolymers and of polycaprolactone, which are collected and drawn on a rotating cylinder. Hydrodynamics and mass balance quantitatively predict the fiber diameter, which is only a function of flow rate and air pressure, with a small correction accounting for viscous dissipation during jet formation, which slightly reduces the jet velocity. Because of the simplicity of the setup, the precise control of the fiber diameter, the positional stability of the exiting ultrafine fiber and the potential to implement arrays of parallel channels for high throughput, this methodology offers significant benefits compared to existing solution-based fiber production methods.